Major phenolic compounds, antioxidant, antimicrobial, and cytotoxic activities of Selinum carvifolia (L.) collected from different altitudes in India - Srivastava, Ravi Prakash; Kumar, Sachin; Singh, Lav; Madhukar, Mayank; Singh, Nitesh; Saxena, Gauri; Pandey, Shivaraman; Singh, Arpit; Devkota, Hari Prasad; Verma, Praveen C.; Shiva, Shatrughan; Malik, Sumira; et al. (Frontiers in Nutrition, 2023)
The present study aims to investigate the major phenolic compounds, antimicrobial, antifungal, antioxidant and cytotoxicity activity in the extracts of the different plant parts (leaves, stem and roots) of Selinum tenuifoliumWall ex C.B. DC. The phenolic compounds from different plant parts were analyzed using HPLC and following were present-chlorogenic acid, gallic acid, rutin, syringic acid, vanillicacid, cinnamic acid, caffeic acid and protocatechuic acid along with other phenolic compounds in all plant parts. The 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay was used to measure in vitro antioxidant activity. In a concentration-dependent way, promising antioxidant activity was reported.3,5-Dinitrosalicylic acid (DNSA) and the Folin–Ciocalteu phenol reagent technique was used to determine reducing sugar content and total phenolic content, respectively.Antimicrobial activity against eight bacterial strains (MIC: 250–1000 µg/ml) was analyzed and stem extract had most potent activity. Antifungal activity was also assessed and potentactivity was reported specially in extract obtained from stem. Cytotoxicity was evaluated using MTT assayin A549 cell line where different dose (0.0625, 0.125, 0.25, 0.5 and 1mg/ml) of leaf, root and stem extracts used.Treatment with these extracts reduced the cell viability indicating that Selinum tenuifolium may possess anticancer potential which can be of great therapeutic value.